Pengaruh Kolom C-Rha terhadap Stabilitas Lereng dengan Pemodelan Centrifuge - Dwi Agrina; Wen-Yi Huang (DPPM Universitas Pelita Bangsa, 2022)
Landslides are natural disasters around the world. Factors such as slope material, rainfall intensity-duration, earthquake, infiltration, and seepage influence the slope stability because of the decrease in resistance forces or the increase of driving force. This research method uses C-RHA columns to improve slope stability as slope strengthening. C-RHA mortar was made of cement, sand and microsilica from fine rice husk ash (RHA). The effect of C-RHA columns on slope stability simulated by a series of centrifuge modeling tests which were conducted at the Experimental Center of Civil Engineering, National Central University. The slope is prepared by moist tamping method at optimum water content about 12% with a mixture material consist of 20% of fine content (kaolinite) and 80% of quartz sand. The C-RHA columns were penetrated perpendicular to the slope surface. During the test, the acceleration was gradually increased and recorded until the slope collapsed. The test results indicate that slopes Test C-0, Test C-4, Test C-9 and Test C-16 fail at 50, 48, 55, and 65 g, respectively. The first tension cracks of Test C-0, Test C-4, Test C-9 and Test C-16 occur at 40, 40, 45, and 55 g, with the depth and distance from crest of slope are 0.328h and 0.324h, 0.273h and 0.300h, 0.350h and 0.327h, and 0.155h and 0.557h, respectively, where h is the slope height. Then, the second cracks appear at 45, 43, 49 and 65 g, respectively to cause the slope failure. From the side view of slope, the decreasing number of C-RHA column spacing will decrease the depletion mass of slope. The depletions mass normalized by the volume of theoretical planar failure wedge with failure angle of Î¸=(Î²+âˆ…)/2 are 67.0 %, 64.5%, 59.3% and 48.6%, respectively. Keywords: Spacing Effect, C-RHA Column, Centrifuge Modeling, Slope Stability